The Ornament of Buddha-Virtues: Translated by Sirisena D. A. Weerasinghe. - Webb, Russell (Buddhist Studies Review, 1980)
The Ornament of Buddha-Virtues: Translated by Sirisena D. A. Weerasinghe. Lassana Printers, Colombo 1976. Distributed by Wilfred M. Gunasekara, 116 Stuart Place, Kollupitiya, Colombo 3. xxxii + 97 pp. Rs. 20/-.